2012
DOI: 10.3329/bjch.v34i3.10361
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Risk Factors of Febrile Seizure – An Update

Abstract: Febrile seizures (FS) are the most common convulsive event in children. This condition has been described since the time of Hippocrates. The etiology of the febrile seizures are still unclear. In FS, there is a strong familial predisposition. This does not exclude infections as a causative factor because subtle genetic polymorphisms have been demonstrated to affect the course of infections. In an earlier review of the world literature (1924-1964), except for roseola infantum, viral infections as a cause of feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…According to other studies, seizure most commonly occurs when children have risk factors such as upper respiratory infection and acute otitis media, parental history of febrile seizure, neonatal hospitalization >30 days, and delayed development. 5,6 On the contrary, one study reported by Parmar et al 7 in Mumbai, India stated that 77.9% parents do not know that seizure can occur during one febrile occasion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to other studies, seizure most commonly occurs when children have risk factors such as upper respiratory infection and acute otitis media, parental history of febrile seizure, neonatal hospitalization >30 days, and delayed development. 5,6 On the contrary, one study reported by Parmar et al 7 in Mumbai, India stated that 77.9% parents do not know that seizure can occur during one febrile occasion.…”
Section: Discussionmentioning
confidence: 96%
“…4 The most common disease that triggers a febrile seizure is ear infections of any cold or viral infection. 5 A febrile seizure can be very frightening for parents. 2 In consequence, parents' ignorance and poor understanding about how to deal with seizure and their anxiety will lead to mismanagement of febrile seizure.…”
Section: Introductionmentioning
confidence: 99%
“…Siblings with history of Febrile Seizure ,showed 10-20% of recurrences. 6 An autosomal dominant inheritance pattern, where found in genes encoding the sodium channel and the gamma amino-butyric acid receptor A. 7 Percentage of recurrence, if one of the parents had history of Febrile Seizure chance of recurrence is about 40%.…”
Section: Pathophysiologymentioning
confidence: 99%
“…FS, the most common type of epileptic seizures in early life world wide (Nakayama and Arinami, 2006;Kundu et al, 2012;Salzmann et al, 2012), is a matter of concern to pediatricians with a total prevalence of 3%-7% in children up to 7 years (Cross, 2012) and a cumulative incidence of 2%-5% in the first 5 years of life (Verity et al, 1985;Visser et al, 2012). FS, occurring during rapid rising of fever (Özaydın et al, 2012) between 6 months and 5 years of age (Klein et al, 2012;Kumari et al, 2012;Martinos et al, 2012;Teran et al, 2012;Zareifar et al, 2012), can be divided into simple forms (only occuring once in 24 h, generalized, and duration < 15 min) and complex forms (recurrent during 24 h, focal, and duration > 15 min) (Kira et al, 2005;Abdel Rasol et al, 2012;French, 2012;Offringa and Newton, 2013;Sasidaran et al, 2012;Scott et al, 2012;Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%